Interplay between physicochemical and mechanical properties of poly(ethylene terephthalate) meshes for hernia repair. Issue 13 (22nd November 2017) - Todros, Silvia; Pavan, Piero Giovanni; Pachera, Paola; Pace, Giuseppe; Di Noto, Vito; Natali, Arturo Nicola
ABSTRACT: Non‐medical‐grade industrial nets are often implemented in developing countries as affordable alternative to surgical meshes for hernia repair. Even if there is clear evidence about their repairing reliability, their physicochemical and mechanical properties have been not fully investigated. This works compares three industrial nets with different textile patterns, and a surgical mesh of the same polymer. Nets are autoclave‐sterilized and characterized through scanning electron microscope, Raman spectroscopy, thermogravimetric analysis, differential scanning calorimetry, and uniaxial tensile tests. Spectral and thermal analyses reveal that all samples are based on poly(ethylene terephthalate). Differences are found in phase conformations with modifications in amorphous, ordered amorphous, and crystalline domains. Changes in material characteristics do not affect mechanical properties, which are mainly ascribable to the textile pattern. Industrial nets show a stiffening behavior different from the almost linear anisotropic response of surgical mesh. However, non‐medical‐grade nets could be potentially applied for surgeries once their biocompatibility and in vivo stability have been evaluated. Non‐medical‐grade industrial nets are used as low‐cost alternative to surgical meshes for hernia repair in less developed countries. Nets sterilization modifies their phase conformation, due to the interaction with water, but do not affect mechanical properties. Even tough industrial nets show a different stiffening behavior, physicochemical characterization confirms a similarity to standard surgical meshes. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46014. Abstract :